(untitled) (KULT_online, 2015)
Based on the work of Pierre Bourdieu, Michel Foucault, Judith Butler, and Bruno Latour, the book Die Instabilität der Praxis. Reproduktion und Transformation des Sozialen in der Praxistheorie by Hilmar Schäfer examines how practice theory could engage with the ambivalent relationship between the stability and instability of social phenomena. In order to find a productive way of dealing with this ambivalence, the book suggests a conceptualization of social practice as specific forms of enduring iteration and provides an analytical vocabulary as well as methodological principals for upcoming practice theoretical studies.